Development of two processes for the synthesis of bridged azabicyclic systems: intermolecular radical addition-homoallylic rearrangements leading to 2-azanorborn-5-enes and neophyl-type radical rearrangements to 2-azabenzonorbornanes. - Hodgson, D; Bebbington, M; Willis, P (2003)
Radical thiol additions to 7-azanorbornadienes give 7-thio-substituted 2-azanorbornenes and Barton deoxygenations of 7-azabenzonorbornanols give 2-azabenzonorbornanes. The processes both involve novel nitrogen-directed radical rearrangements. The kinetics and mechanisms of the reactions are also discussed.